2001
DOI: 10.1002/yea.731
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae YCRO17c/CWH43 encodes a putative sensor/transporter protein upstream of the BCK2 branch of the PKC1‐dependent cell wall integrity pathway

Abstract: The Saccharomyces cerevisiae cwh43-2 mutant, originally isolated for its Calcofluor white hypersensitivity, displays several cell wall defects similar to mutants in the PKC1-MPK1 pathway, including a growth defect and increased release of b-1,6-glucan and bglucosylated proteins into the growth medium at increased temperatures. The cloning of CWH43 showed that it corresponds to YCR017c and encodes a protein with 14-16 transmembrane segments containing several putative phosphorylation and glycosylation sites. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 55 publications
3
36
0
Order By: Relevance
“…Cwh43 is a putative sensor/ transporter protein that acts upstream of the BCK2 branch of the PKC1-dependent cell wall integrity pathway and is involved in cell wall biogenesis (29). The principal structural feature of Cwh43 is the presence of 14 to 16 transmembrane segments and several putative glycosylation and phosphorylation sites.…”
Section: Discussionmentioning
confidence: 99%
“…Cwh43 is a putative sensor/ transporter protein that acts upstream of the BCK2 branch of the PKC1-dependent cell wall integrity pathway and is involved in cell wall biogenesis (29). The principal structural feature of Cwh43 is the presence of 14 to 16 transmembrane segments and several putative glycosylation and phosphorylation sites.…”
Section: Discussionmentioning
confidence: 99%
“…Through a multicopy gene expression strategy, we have not been able to find any multicopy suppressor that could overcome the synthetic growth defect of a knr4∆bck1∆ or knr4∆slt2∆. Also overexpression of BCK2, which encodes a protein known to interact and to share partially redundant functions with Knr4 (Martin-Yken et al, 2001;Basmaji et al, 2006) did not rescue growth in these double mutants (data not shown). Altogether, and assuming that all yeast genes were covered in the suppression experiments, these genetic data indicate that there is no other protein that can perform a redundant function with Knr4 in this context.…”
Section: Functional Analysis Of Knr4 Proteinmentioning
confidence: 96%
“…Among the top 10 deletion mutants sensitive to poacic acid, we detected enrichment for genes involved in the gene ontology (GO) category fungal-type cell wall organization (P < 0.01). These mutants included deletion alleles of BCK1 (bypass of C kinase), which encodes an MAPKKK in the Pkc1p (protein kinase C) cell wall integrity signaling pathway (PKC pathway); CWH43, which encodes a membrane protein involved in cell wall biogenesis and its null mutation is synthetically lethal with PKC1 mutants (29); ROM2 (Rho1 multicopy suppressor), a GDP/GTP exchange factor for Rho1p and another component of the PKC pathway; and ACK1, which seems to encode an upstream activator of Pkc1p and has a physical interaction with Rom2p. Overall, the PKC pathway was the most sensitive pathway to poacic acid (Pathway z score = −7.85) (Fig.…”
Section: Chemical Genomics Predict That Poacic Acid Targets the Fungamentioning
confidence: 99%